The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins